Study on Moringa Germplasm Collection and Screening in Southern Ethiopia - Mulugeta, Getachew (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2018)
Moringa stenopetala Bac. and Moringa oleifera Lam germplasm collection and screening trial was conducted in three locations at Konso, Arba Minch and Hawassa in SNNPR, Ethiopia. The study was carried out for three consecutive years (2005-2007) to assess natural variability of agronomic yield and to generate germplasm pool for subsequent studies on genetic improvement. Moringa stenopetala seeds were collected from sites in Konso, Arba Minch and Kucha areas whereas the seeds of Moringa oleifera were obtained from ECHO-seed bank. From each site of Moringa stenopetala, 1000 seeds were collected from a random sample of up to 20 trees. The location of each tree accession was recorded with GPS. The experiment comprised 33 Moringa accessions, 28 belonging to indigenous specie of Moringa stenopetala while 5 to exotic Moringa oleifera species. The accessions were compared using Randomized Complete Block Design with four replications after three years of establishment. The data was analyzed with the help of SAS software packages. The results revealed that there were a significant variation in accession Konso Nagayle at three tested sites, with mean values of survival rate, mean height, mean collar diameter, mean number of branches per tree and mean dry leaf biomass per tree were 98.88%, 4.53m, 28.56cm, 96.99 and 47.62kg, respectively. Therefore, the native Moringa accession Konso Nagayle could be recommended for further genetic pool improvement and leaf production at Konso, Arba Minch and, Hawassa areas.